Knowledge, Attitude and Practice of Pharmacy Professionals Against Dispensing Antibiotics Without Prescription in Ethiopia - Haile KT; Yabeyu AB (Dove Medical Press, 2022)
Kaleab Taye Haile,1 Abdella Birhan Yabeyu2 1Department of Pharmaceutics and Social Pharmacy, University of Gondar, Gondar, Ethiopia; 2Department of Pharmacy, Ambo University, Ambo, EthiopiaCorrespondence: Kaleab Taye Haile, Department of Pharmaceutics and Social Pharmacy, University of Gondar, Gondar, Ethiopia, Email teezysam@gmail.comIntroduction: Antibiotic resistance is a global public health threat that warrants immediate intervention. Dispensing of antibiotics without prescription (DAWP), is an inappropriate practice that contributes significantly to the emergence and spread of antibiotic resistance. The current study aimed to assess the knowledge, attitude and practice of community pharmacists and pharmacy assistants towards DAWP.Methods: A cross-sectional study was conducted, and data was collected from community pharmacists and pharmacy assistants during the eighth national pharmacist's day, which was held on December 4, 2021, in Addis Ababa, Ethiopia. A pre-tested self-administered questionnaire comprise of four sections (socio-demographic characteristics, and knowledge, attitude and practice towards DAWP) was used. The data was analyzed using SPSS version 26 and descriptive statistics (mean, percentage, standard deviation) were computed. Binary logistic regression was used to predict determinates of DAWP.Results: A total of 175 community pharmacy professional were invited in the study, with 158 (111 pharmacists and 47 pharmacy assistants) completing the survey for 90.3% response rate. Most of the participants (86.7%) were aware that DAWP is illegal in Ethiopia. Despite their knowledge, the extent of DAWP was found to be 67.7%. The most common reason given by study participants for DAWP was that most patients do not want to consult prescribers unless the infection appears serious (53.2%). Pharmacy professionals with educational background of masters and above (AOR= 0.354, 95% CI: 0.013- 0.744, P= 0.045), and with two to five years of working in community pharmacy (AOR= 0.745, 95% CI: 0.595- 0.933, P= 0.010) had a lower tendency to DAWP, respectively.Conclusion: Despite majority of pharmacy professional are aware that DAWP is illegal and contributes to antibiotic resistance, they commonly DAWP for common cold and diarrheal diseases. Strict enforcement of existing antibiotic supply policies, and ongoing educational support for community pharmacy professionals on the judicious use of antibiotics is recommended.Keywords: community pharmacy, dispensing antibiotics without prescription, Ethiopia, pharmacy professionals